QUALITY OF LIFE OF TEACHERS: A STUDY IN HIGHER EDUCATION INSTITUTIONS OF THE CITY OF PALMAS TO (Fiep Bulletin - online, 2010)
Due to its specific characteristics, there are various factors in teaching that have direct influence in the quality of peoples' lives. The aim of this study is to research Professional profile and the quality of life of teachers in the city of Palmas, state of Tocantins, oriented by the guidelines of the World Health Organisation. The practical part of this study will be of an exploratory nature correlated to the descriptive method. Considering the problematic of the present study as well as its research universe, we decided to opt for the quantitative and inquiry methods through the use of two questionnaires. One hundred and ninety teachers were interviewed. The results obtained therein reveal that, in a subjective analysis teachers tend to generally qualify their quality of life as good. In the different domains, we are revealed that, in the physical and psychological areas men teachers have better quality of life than women teachers.